Preparation of Aspirin Nanosuspension by Antisolvent Precipitation Method - Van Khanh, Nguyen; Van Thuong, Vu; Thanh Hai, Nguyen; Anh Tuan, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 3DO - 10.25073/2588-1132/vnumps.4294, 2021)
This study aims to enhance the dissolution rate of a poorly-soluble drug, aspirin, by fabricating aspirin nanosuspensions using the anti-solvent precipitation. The  study investigates the effect of the type of solvents, solvent to anti-solvent ratio, drug concentration, machines, stirring speed, ultrasonication technique and the temperature of solvent on the particle size and polydispersity index. The characterization of the original aspirin powder and nanoparticles was evaluated by differential scanning calorimetry and in vitro dissolution test. The results indicate that the selected formulation showed the smallest mean size of 228.2 ± 24.6 nm and a zeta potential of - 40.3 ± 2.5 mV. The differential scanning calorimetry analysis demonstrates that aspirin nanoparticles possessed lower crystallinity than the raw aspirin powder. The dissolution of nanoparticle was significantly higher compared with the original drug in the in vitro dissolution test. Keywords : Aspirin, nanosuspension, anti-solvent precipitation, differential scanning calorimetry, dissolution. References  [1] G. C. Curhan, A. J. Bullock, S. E. Hankinson, W. C. Willett, F. E. Speizer, M. J. Stampfer, Frequency of Use of Acetaminophen, Nonsteroidal Anti-Inflammatory Drugs, and Aspirin in US Women, Pharmacoepidemiol Drug Saf, Vol. 11, No. 8, 2002, pp. 687-693, https://doi.org/10.1002/pds.732. [2] Antithrombotic Trialists (ATT) Collaboration, Aspirin in the Primary and Secondary Prevention of Vascular Disease: Collaborative Meta-analysis of Individual Participant Data from Randomised Trials, The Lancet, Vol. 373, 2009, pp. 1849-1860, https://doi.org/10.1016/S0140-6736(09)60503-1. [3] Y. Golfar, A. Shayanfar, Prediction of Biopharmaceutical Drug Disposition Classification System (BDDCS) by Structural Parameters, J Pharm Pharm Sci, Vol. 22, No. 1, 2019, pp. 247-269, https://doi.org/10.18433/jpps30271. [4] S. Luo, H. Man, X. Jia, Y. Li, A. Pan, X. Zhang, Y. Songa, Preparation and Characterization of Acetylsalicylic Acid/chitosan Nanoparticles and its Antithrombotic Effects, Des Monomers Polym, Vol. 21, No. 1, 2018, pp. 172-181, https://doi.org/10.1080/15685551.2018.1534317. [5] S. Ahmad, H. Rashid, Q. Jalil, S. Munir, B. Barkatullah, S. Khan, R. Ullah, A. Shahat, H. M. Mahmood, A. A. N. A. A. Mishari, A. B. Bari, Polymers Encapsulated Aspirin Loaded Silver Oxide Nanoparticles: Synthesis, Characterization and its Bio-Applications, Sains Malaysiana, Vol. 48, No. 9, 2019, pp. 1887-1897, http://dx.doi.org/10.17576/jsm-2019-4809-09. [6] T. H. Gugu, S. A. Chime, A. A. Attama, Solid Lipid Microparticles: An Approach for Improving Oral Bioavailability of Aspirin, Asian Journal of Pharmaceutical Sciences, Vol. 10, No. 5, 2015, pp. 425-432, https://doi.org/10.1016/j.ajps.2015.06.004. [7] O. Dandah, M. Najafzadeh, M. Isreb, R. Linforth, C. Tait, A. Baumgartner, D. Anderson, Aspirin and Ibuprofen, in Bulk and Nanoforms: Effects on DNA Damage in Peripheral Lymphocytes from Breast Cancer Patients and Healthy Individuals, Mutation Research/Genetic Toxicology and Environmental Mutagenesis, Vol. 826, 2018, pp. 41-46, https://doi.org/10.1016/j.mrgentox.2017.12.001. [8] C. Keck, R. Muller, Drug Nanocrystals of Poorly Soluble Drugs Produced by High Pressure Homogenisation, Eur J Pharm Biopharm, Vol. 62, No. 1, 2006, pp. 3-16, https://doi.org/10.1016/j.ejpb.2005.05.009. [9] B. Vaneerdenbrugh, G. Vandenmooter, P. Augustijns, Top-down Production of Drug Nanocrystals: Nanosuspension Stabilization, Miniaturization and Transformation into Solid Products, Int J Pharm, Vol. 364, No. 1, 2008, pp. 64-75, https://doi.org/10.1016/j.ijpharm.2008.07.023. [10] H. Dewaard, W. Hinrichs, H. Frijlink, A Novel Bottom–up Process to Produce Drug Nanocrystals: Controlled Crystallization During Freeze-drying, J Control Release, Vol. 128, No. 2, 2008, pp. 179-183, https://doi.org/10.1016/j.jconrel.2008.03.002. [11] E. M. Michal, A. H. Margaret, P. J. Keith, O. W. I. Robert, Drug Nanoparticles by Antisolvent Precipitation: Mixing Energy versus Surfactant Stabilization, Langmuir, Vol. 22, No. 21, 2006, pp. 8951-8959, https://doi.org/10.1021/la061122t. [12] S. Sana, K. Boodhoo, V. Zivkovic, Production of Starch Nanoparticles through Solvent-antisolvent Precipitation in a Spinning Disc Reactor, Green Processing and Synthesis, Vol. 8, No. 1, pp. 507-515, https://doi.org/10.1515/gps-2019-0019. [13] X. Zhang, H. Chen, F. Qian, Y. Cheng, Preparation of Itraconazole Nanoparticles by Anti-solvent Precipitation Method Using a Cascaded Microfluidic Device and an Ultrasonic Spray Drier, Chemical Engineering Journal, Vol. 334, 2018, pp. 2264-2272, https://doi.org/10.1016/j.cej.2017.12.002. [14] Y. Dong, W. K. Ng, S. Shen, S. Kim, R. B. H. Tan, Preparation and Characterization of Spironolactone Nanoparticles by Antisolvent Precipitation, Int J Pharm, Vol. 375, No. 1-2, 2009, pp. 84-88, https://doi.org/10.1016/j.ijpharm.2009.03.013. [15] D. H. Kuk, E. S. Ha, D. H. Ha, W. Y. Sim, S. K. Lee, J. S. Jeong, J. S. Kim, I. Baek, H. Park, D. H. Choi, J. W. Yoo, S. H. Jeong, S. J. Hwang, M. S. Kim, Development of a Resveratrol Nanosuspension Using the Antisolvent Precipitation Method without Solvent Removal, Based on a Quality by Design (QbD) Approach, Pharmaceutics, Vol. 11, No. 12, 2019, pp. 1-22, https://doi.org/10.3390/pharmaceutics11120688. [16] D. Liu, H. Xu, B. Tian, K. Yuan, H. Pan, S. Ma, X. Yang, W. Pan, Fabrication of Carvedilol Nanosuspensions Through the Anti-Solvent Precipitation–Ultrasonication Method for the Improvement of Dissolution Rate and Oral Bioavailability, AAPS Pharm Sci Tech, Vol. 13, No. 1, 2012, pp. 295-304, https://doi.org/10.1208/s12249-011-9750-7. [17] H. Kathpalia, S. Juvekar, S. Shidhaye, Design and In Vitro Evaluation of Atovaquone Nanosuspension Prepared by pH Based and Anti-solvent Based Precipitation Method, Colloid and Interface Science Communications, Vol. 29, 2019, pp. 26-32, https://doi.org/10.1016/j.colcom.2019.01.002. [18] D. B. Shelar, S. K. Pawar, P. R. Vavia, Fabrication of Isradipine Nanosuspension by Anti-solvent Microprecipitation-high-pressure Homogenization Method for Enhancing Dissolution Rate and Oral Bioavailability, Drug Deliv Transl Res, Vol. 3, No. 5, 2013, pp. 384-391, https://doi.org/10.1007/s13346-012-0081-3. [19] M. Kakran, N. G. Sahoo, L. Li, Z. Judeh, Fabrication of Quercetin Nanoparticles by Anti-solvent Precipitation Method for Enhanced Dissolution, Powder Technology, Vol. 223, 2012, pp. 59-64, https://doi.org/10.1016/j.powtec.2011.08.021. [20] A. Affonso, V. R. Naik, Microcrystallization Methods for Aspirin, Mebutamate, and Quinine Sulfate, Journal of Pharmaceutical Sciences, Vol. 60, No. 10, 1971, pp. 1572-1574, https://doi.org/10.1002/jps.2600601032. [21] M. Kakran, N. G. Sahoo, I. L. Tan, L. Li, Preparation of Nanoparticles of Poorly Water Soluble Antioxidant Curcumin by Antisolvent Precipitation Methods, J Nanopart Res, Vol. 14, No. 3, 2012, pp. 3-11, https://doi.org/10.1007/s11051-012-0757-0. [22] C. Li, C. Li, Y. Le, J. F. Chen, Formation of Bicalutamide Nanodispersion for Dissolution Rate Enhancement, International Journal of Pharmaceutics, Vol. 404, No. 1-2, 2011, pp. 257-263, https://doi.org/10.1016/j.ijpharm.2010.11.015. [23] A. S. Paulino, G. Rauber, C. E. M. Campos, M. H. P. Maurício, R. R. de Avillez, G. Capobianco, S. G. Cardoso, S. L. Cuffini, Dissolution Enhancement of Deflazacort Using Hollow Crystals Prepared by Antisolvent Crystallization Process, European Journal of Pharmaceutical Sciences, Vol. 49, No. 2, 2013, pp. 294-301, http://dx.doi.org/10.1016/j.ejps.2013.03.014. [24] S. Yee. Wong, Y. Cui, A. S. Myerson, Contact Secondary Nucleation as a Means of Creating Seeds for Continuous Tubular Crystallizers, Crystal Growth & Design, Vol. 13, No. 6, 2013, pp. 2514-2521, https://doi.org/10.1021/cg4002303. [25] Y. Cui, A. S. Myerson, Experimental Evaluation of Contact Secondary Nucleation Mechanisms, Crystal Growth & Design, Vol. 14, No. 10, 2014, pp. 5152-5157, https://doi.org/10.1021/cg500861f. [26] J. Tao, S. F. Chow, Y. Zheng, Application of Flash Nanoprecipitation to Fabricate Poorly Water-Soluble Drug Nanoparticles, Acta Pharmaceutica Sinica B, Vol. 9, No. 1, 2019, pp. 4-18, https://doi.org/10.1016/j.apsb.2018.11.001. [27] B. Sinha, R. H. Müller, J. P. Möschwitzer, Bottom-up Approaches for Preparing Drug Nanocrystals: Formulations and Factors Affecting Particle Size, Int J Pharm, Vol. 453, No. 1, 2013, pp. 126-141, https://doi.org/10.1016/j.ijpharm.2013.01.019. [28] H. X. Zhang, J. X. Wang, Z. B. Zhang, Y. Le, Z. G. Shen, J. F. Chen, Micronization of Atorvastatin Calcium by Antisolvent Precipitation Process, Int J Pharm, Vol. 374, No. 1-2, 2009, pp. 106-113, https://doi.org/10.1016/j.ijpharm.2009.02.015. [29] A. L. Abhijit, R. P. Sanjaykumar, Antisolvent Crystallization of Poorly Water Soluble Drugs, International Journal of Chemical Engineering and Applications, Vol. 4, No. 5, 2013, pp. 337-341, https://doi.org/10.7763/IJCEA.2013.V4.321. [30] Z. Zhang, Z. Shen, J. Wang, H. Zhao, J. Chen, J. Yun, Nanonization of Megestrol Acetate by Liquid Precipitation, Industrial and Engineering Chemistry Research, Vol. 48, No. 18, 2009, pp. 8493-8499, https://doi.org/10.1021/ie900944y. [31] M. Kakran, N. G. Sahoo, L. Li, Z. Judeh, Particle Size Reduction of Poorly Water Soluble Artemisinin via Antisolvent Precipitation with a Syringe Pump, Powder Technology, Vol. 237, 2013, pp. 468-476, https://doi.org/10.1016/j.powtec.2012.12.029. [32] A. F. Kardos, J. Toth, J. Gyenis, Preparation of Protein Loaded Chitosan Microparticles by Combined Precipitation and Spherical Agglomeration, Powder Technology, Vol. 244, 2013, pp. 16-25, https://doi.org/10.1016/j.powtec.2013.03.052. [33] Z. Wang, J. Chen, Y. Le, Z. Shen, Preparation of Ultrafine Beclomethasone Dipropionate Drug Powder by Antisolvent Precipitation, Industrial and Engineering Chemistry Research, Vol. 46, No. 14, 2007, pp. 4839-4845, https://doi.org/10.1021/ie0615537. [34] I. Aghrbi, V. Fülop, G. Jakab, N. K. Szab, E. Balogh, I. Antal, Nanosuspension with Improved Saturated Solubility and Dissolution Rate of Cilostazol and Effect of Solidification on Stability, Journal of Drug Delivery Science and Technology, Vol. 61, 2020, pp. 1-10, https://doi.org/10.1016/j.jddst.2020.102165. [35] P. Costa, J. M .S. Lobo, Modeling and Comparison of Dissolution Profiles, European Journal of Pharmaceutical Sciences, Vol. 13, No. 2, 2001, pp. 123-133, https://doi.org/10.1016/S0928-0987(01)00095-1. [36] A. Viçosa, J. Letourneau, F. Espitalier, M. Ré, An Innovative Antisolvent Precipitation Process as a Promising Technique to Prepare Ultrafine Rifampicin Particles, Journal of Crystal Growth, Vol. 342, No. 1, 2012, pp. 80-87, https://doi.org/10.1016/j.jcrysgro.2011.09.012. [37] The International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use, Validation of Analytical Procedures: Text and Methodology Q2(R1), 2005, pp. 6-13. [38] J. B. Dressman, A. Nair, B. Abrahamsson, D. M. Barends, D. W. Groot, S. Kopp, P. Langguth, J. E. Polli, V. P. Shah, M. Zimmer, Biowaiver Monograph for Immediate-release Solid Oral Dosage Forms: Acetylsalicylic Acid, Journal of Pharmaceutical Sciences, Vol. 101, No. 8, 2012, pp. 2653-2667, https://doi.org/10.1002/jps.23212. [39] T. Yuka, M. Mihoko, Y. Hiroshi Y, O. Shino, A. Hiroaki, T. Kazufumi, T. Katsuo, I. Masayuki, Y. Masashi, M. Yusuke, Intergrowth of Two Aspirin Polymorphism Observed with Raman Spectroscopy, Journal of Crystal Growth, Vol. 532, 2020, pp. 1-28, https://doi.org/10.1016/j.jcrysgro.2019.125430.